The Influence of Trademark Bullying on Brand Owners of Large Businesses and UMKM Actors Based on Positive Law in Indonesia - Lainun Hilmansyah, Shilfa; Ratna Permata, Rika; Safiranita, Tasya (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This study analyzes the impact of Trademark Bullying in influencing business competition in Indonesia on business owners and efforts can be made in the event of legal uncertainty for business actors who own UMKM brands in the event of Trademark Bullying based on the applicable positive law. The stidy used juridical normative method. Trademark Bullying practices also involve threats of litigation or legal reporting to the authorities. Where if this happens small business brand owners will be greatly disadvantaged because of the large costs required if this takes place in the litigation process because small business brand owners do not have the financial capacity to fight legally, so in the end they give up using the brand they own. legally due to the lawsuit process filed by the perpetrator of Trademark Bullying.